A Study On School Readiness Of The Children In ECCE Centres Of South Garo Hills Baghmara District - Keri Grace Laloo; Prof. K.C. Kapoor (Revista Electronica de Veterinaria, 2024)
Children in the age group of 3-6 years require specific learning opportunities in the non-formal settings. Anganwadi provide the Early Childhood Education through play-way methods which stimulate the mental development and satisfy the curiosity of the children. Children learn to play together, recite rhymes and songs and learn the concepts of colour and the surroundings which form the basic for sound primary education in later years.Readiness means the child’s ability to participate and succeed in the beginning of schooling which includes the child’s ability to accomplish and engage in processes associated with schooling, whether Nursery school, Preschool, Kindergarten. School readiness means a deficit which is detriment for success in schools. School readiness is the type of schooling which allows the child to get ready for primary school. The child is able to read and write properly. The Pre-school is an early childhood program in which children combine learning with play and programs run by professional trained teacher or coordinator. Children are most commonly enrolled in Pre-school between the ages of three to five. In the State of Meghalaya, pre-school is commonly known Pre-primary school, playschool or Kindergarten which is an educational institution establishment or learning space offering early childhood care education to children before they begin compulsory education at primary school. Therefore, the objective is to study the school readiness of the children in the ECCE centres of South Garo Hills District. The researcher adopted descriptive cum normative survey method and cross sectional research design for the completion of this study. The total population of pre-school centres is recorded 3265 learners out of which 5 percent was taken as the sample size for the study and it came out to be 163 pre-school children. The sample was selected by making a simple random sampling technique. School readiness scale developed by Centre for Early Childhood Education and Development (CECED), Ambedkar University Delhi was used to collect the required data and analyzed the data by applying the descriptive and inferential statistical techniques. The major findings of the study came out to be satisfactory and functioning the school readiness effectively.